AUDIT QUALITY: COMPETENCE, PROFESSIONAL SKEPTICISM, WORKLOAD, AND AUDITOR TIME PRESSURE - Raihan, Ahmad Daffa; Setiyawati, Hari (Kesatuan Press, 2025)
This study examines the impact of competence, professional skepticism, workload, and time pressure on audit quality within Accounting Firms (KAP) in West Jakarta. Motivated by recent high-profile audit failures, this research seeks to address concerns about the effectiveness of current auditing practices. West Jakarta, known for its rapid business growth and a high concentration of KAPs, provides a relevant and diverse setting for this study. Data were collected from 100 auditors registered with the Indonesia Institute of Public Accountants, using a convenience sampling method, and analyzed with Smart PLS version 4.0. The findings indicate that while auditor competence, workload, and time pressure do not significantly impact audit quality, professional skepticism significantly enhances audit quality. It underscores the critical role of professional skepticism in maintaining high audit standards and preventing failures, particularly in high-pressure and high-workload environments.